Effect of microstructure evolution in austenite zone on mechanical properties of Fe-10Mn-5.5Al-0.25C steel. (November 2020) - Peng, Wei; Gao, Xinqiang; Guo, Xiaofei; Lu, Hengchang; Li, Guangshi; Xiao, Xueshan; Xu, Dexiang; Wei, Xicheng; Dong, Han
Abstract: The microstructure of Fe-Mn-Al-C alloys is largely influenced by heat treatment, which leads to different mechanical properties. The current work investigated the microstructure evolution in the austenite zone in a low density steel Fe-10Mn-5.5Al-0.25C at the heat treatment temperature range of 850 °C–1000 °C. The microstructure features have been characterized by SEM, TEM. The results indicate that the soaking temperature has great influence on the room-temperature mechanical properties, even promotes austenite-to-martensite transformation at 1000 °C heat treatment. The increased temperature and austenite zone fraction degrade the stability of austenite, whilst the small B2 phase shows no detrimental effect on mechanical properties. The product of tensile strength and elongation increases from 28 to 50 GPa% is due to multiple deformation mechanisms with austenite zone fraction increased. And the transformed martensite at 1000 °C significantly decreases the mechanical properties. So, the improved mechanical properties maybe attributed to the coordination function of dislocations pile-up and cut through the B2 phase, and strengthened TWIP effect as heat treatment temperature below 1000 °C. Graphical abstract: Unlabelled Image Highlights: Microstructure evolution in austenite zone promote multiple strengthening mechanisms by controlling soaking temperature. Quenched martensite formed at the soaking temperature of 1000 °C and deteriorated the material ductility. B2 phase shows good benefits on mechanical properties of low-density steel. Dislocations can stack at B2 phase interfaces or cut through it.